Catalytic Ability Comparison of Five Transition Metal Clusters (Zn, Cu, Fe, Ni, and Ru) for Heat‐Induced Graphene Etching by Ab Initio Molecular Dynamics Simulations. Issue 1 (23rd November 2021) - Bie, Jie; Wang, Jinlan; Chen, Shuang; Fa, Wei
Abstract: Graphene can be widely utilized as a substrate to support various transition metal (TM) nanoclusters or nanoparticles for surfaced‐supported catalysis, such as electrocatalysis or photovoltaics. The subtle interactions between TM and graphene carbon atoms are expected to be crucial in TM–graphene nanocomposites to affect their growth morphologies and final functionalities. Here, the morphology evolution and catalytic ability of five ultrafine TM (Zn, Cu, Fe, Ni, and Ru) clusters with 48 atoms on graphene etching are investigated by using ab initio molecular dynamics (AIMD) simulations. It is found that three factors, i.e., TM cluster type, operation temperature, and graphene edge type, play important roles in the catalytic behaviors of TM clusters for heat‐induced graphene etching. The results are helpful in locating the catalytic performance of TM clusters in graphene cutting and ensuring stability of TM–graphene nanocomposites in device applications. Abstract : The transition metal (TM) cluster type, graphene edge type, and operation temperature are found to synergically affect the catalytic performance of TM clusters in graphene etching. Controlling the delicate balance of these three factors can improve the stability of TM–graphene‐nanocomposite‐based devices or induce possible TM‐cluster‐catalyzed graphene cutting.